1979
DOI: 10.1111/j.1559-1816.1979.tb02714.x
|View full text |Cite
|
Sign up to set email alerts
|

The Air Pollution Experience and Physical Aggression1

Abstract: Sixty undergraduate males delivered electric shocks to a confederate as punishment for making errors on a learning task. Half did so after being exposed to an aggressive model, whereas the other half did so without being exposed. Shocks were delivered from a room whose atmosphere was either unpolluted or contaminated by a moderately unpleasant odor (ethyl mercoptan) or an extremely obnoxious stench (ammonium sulfide). As hypothesized, the moderately unpleasant pollutant facilitated higher levels of aggression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 26 publications
3
45
0
2
Order By: Relevance
“…For example, Erlichman and Halpern (1988) found that exposure to unpleasant smells triggered retrieval of unhappy memories, whereas exposure to pleasant smells triggered happy memories. Rotton (1979) found that men behaved more aggressively following exposure to an unpleasant smell than following exposure to a smell-free environment. R. A.…”
Section: Smellmentioning
confidence: 95%
“…For example, Erlichman and Halpern (1988) found that exposure to unpleasant smells triggered retrieval of unhappy memories, whereas exposure to pleasant smells triggered happy memories. Rotton (1979) found that men behaved more aggressively following exposure to an unpleasant smell than following exposure to a smell-free environment. R. A.…”
Section: Smellmentioning
confidence: 95%
“…Les odeurs peuvent induire des effets secondaires, comme des nausées, des troubles de la concentration, de l'appétit, des insomnies et surtout de l'inconfort. De nombreuses études ont montré que l'exposition à des atmosphères malodorantes, bien que non toxiques, affecte, chez un individu, l'évalua-tion des qualités de l'environnement, la sympathie envers les autres et renforce les sentiments d'anxiété, de fatigue et de tristesse (Rotton J. et al, 1979 ;Shusterman, 1992 ;Laing DG. et al, 1994 ;Schiffman, 1998 ;Le Guérer, 1998).…”
Section: Quels Sont Les Effets Sur Les Riverains ?unclassified
“…Similarly, pleasant smell increased helping behavior, even without a direct request for help, in a study by Guéguen (2001). Rotton, Frey, Barry, Milligan, and Fitzpatrick (1979) performed an experiment in which subjects could punish their partners for making mistakes in a group task. Participants in a neutral odor condition desired to punish their partners to a lesser extent than those surrounded by an unpleasant scent.…”
Section: Situational Factors Related To Pro-social Behaviors (Odors Amentioning
confidence: 99%